Immature stages of Neotropical Hydrophilidae (Coleoptera): Hydramara argentina (Knisch, 1925) and Hemiosus bruchi Knisch, 1924 - Archangelsky, Miguel (2000)
The egg case and pupa of Hydramara argentina and the larva, egg case and pupa of Hemiosus bruchi are described and illustrated for the first time. Information on the biology of these two species is provided. Couplets are included to interpolate larvae of Hemiosus and first intars of Hydramarain the recent key to immatures of hydrophiloid genera of the New World.